Quantifying the source–sink balance and carbohydrate content in three tomato cultivars - Li, Tao; Heuvelink, Ep; Marcelis, Leo F. M. (Frontiers in Plant Science, 2015)
The effect of supplementary lighting on plant growth depends on the balance between assimilate production in source leaves and the overall capacity of the plants to use assimilates. This study aims at quantifying the source-sink balance and carbohydrate content of three tomato cultivars differing in fruit size, and to investigate to what extent the source/sink ratio correlates with the potential fruit size. Cultivars Komeett (large size), Capricia (medium size) and Sunstream (small size, cherry tomato) were grown at similar crop management as in commercial practice. Supplementary lighting was applied. Source strength was estimated from total plant growth rate using periodic destructive plant harvests in combination with the crop growth model TOMSIM. Sink strength was estimated from potential fruit growth rate which was determined from non-destructively measuring the fruit growth rate at non-limiting assimilate supply, growing only one fruit on each truss. Carbohydrate content in leaves and stems were periodically determined. During the early growth stage, ‘Komeett’ and ‘Capricia’ showed sink limitation and ‘Sunstream’ was close to sink limitation. Subsequently, during the fully fruiting stage all three cultivars were strongly source-limited as indicated by the low source/sink ratio (average source/sink ratio from 50 days after planting onwards was 0.17, 0.22 and 0.33 for ‘Komeett’, ‘Capricia’ and ‘Sunstream’, respectively). Carbohydrate content in leaves and stems increased linearly with the source/sink ratio. We conclude that under high irradiance tomato plants are sink-limited during their early growth stage, the level of sink limitation differs between cultivars but is not correlated with their potential fruit size. During the fully fruiting stage tomato plants are source-limited and the extent of source limitation of a cultivar is positively correlated with its potential fruit size.